Gendered Violence against Women and Girls on Social Media: A Critical Examination of Online Harassment and Abuse - Awais Ur Rahman ,; Aneela Hakeem Rajpar,; Nimra Abbas,; Komal Saleem,; Rida Qureshi,; Rubia Batool, (Dialogue Social Science Review (DSSR), 2024)
In this study, we examined gendered violence against women and girls on social media – the types of violence, the consequences of such violence, and the response approach taken by the platforms. The objective of our research was twofold: first, to understand the different forms of aggressions on the net, like cyber stalking, sexually harassing, or using hate speech; second, to discuss the impact of those behaviors on the psychological, emotional and the social aspects of the victim. The data for this paper was gathered through two-focus group discussions and one- hundred respondents were interviewed using semi-structured interviews. research revealed that 72% of respondents reported that they had faced sexual harassment; of them 40% expressed a direct impact of this abuse with upshot among which were anxiety and depression. Additionally, 65% of participants expressed their discontent with specific actions taken by social platform confessing that they did not respond properly to abuse. It is for this reason that this research calls for the need to enhance the observation and execution of the platform polices and intercedings against gendered violence online and related social consequences, including perpetuating gender inequalities and suppressing women’s voices online.